Biomimmetic ZrO2@PdO nanocomposites: fabrication, characterization, and water splitting potential exploration. (17th February 2022) - Zahra, Taghazal; Ahmad, Khuram Shahzad; Zequine, Camila; Gupta, Ram; Thomas, Andrew; Malik, Mohammad Azad; Iram, Sadia; Ali, Daoud
Summary: Semiconducting metal oxide nanostructures have the potential to play a significant role for introducing a new podium for alternative energy technologies, such as energy storage and conversion via photovoltaic array, solar fuels, and water electrolysis. To be able to build high‐performance fuel cells and electrocatalysts to meet energy demand, it is critical to develop abundant and cheap electrocatalysts to address fossil fuel reduction and the energy crisis. Current study reports the first investigation on nanocomposite of Zirconia and palladium oxide (ZrO2 @PdO) as an electrode material synthesized by a biomimetic approach. Biosynthesized ZrO2 @PdO nanocomposites had direct band gaps of 4.5 and 3.5 eV, as measured by ultraviolet spectrophotometry capped by organic functional groups as revealed by Fourier‐transform infrared spectroscopy. Formation of oxide nanoparticles was confirmed through UV‐Vis spectroscopy with peaks exhibition between 300 and 400 nm. Polycrystalline phase patterns were determined by x‐ray diffraction with average crystallite sizes of 12 nm. Scanning electron micrographs of nanocomposites revealed granular and uniform grain shapes, with strong signals for Zr, Pd, and O exposed by energy dispersive x‐ray spectroscopy. X‐ray photoelectron spectroscopy successfully revealed the capping of phytocompounds (C1s) as well as confirmed the composition of material with strong signals of Pd, Zr, and O1s. Electrochemical investigation included linear sweep voltammetry and electrochemical impedance spectroscopic (EIS) studies. The electrode performed well, with low overpotential value as well as Tafel slope value (64 mV/dec), signifying its effectiveness as oxidation catalyst. The Nyquist plot from EIS with an arc radius demonstrated the occurrence of resistance mechanism arising from interfacial region of electrode surface with charge transfer resistance ( R ct ) of only 3.23 Ω. ZrO2 @PdO did not perform well for hydrogen evolution reaction under the same operating conditions, however, can be improved by optimizing the parameters. Active to electrochemical application manifested ZrO2 @PdO a potential candidate for photovoltaic devices in term of economic viability and sustainability in comparison to environmentally harmful pathways.